The Implementation of Jigsaw Type Cooperative Learning Model to Improve Student Learning Outcomes of Senior High School Seulimun in Aceh Besar Regency - Ismail Ismail (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Application of Jigsaw Cooperative Learning Model to Improve Learning Outcomes of Social Science Learning in 11th grade social studies (IPS-2) Senior High School Seulimum Aceh Besar Regency. The aim of the research is to improve student learning outcomes in learning Social Sciences in 11th grade IPS-2 Senior High School Seulimum Aceh Besar Regency in the 2017/2018 school year by using Jigsaw cooperative learning, the subjects in this study were all students of 11th grade IPS-2 Senior High School Seulimum Aceh Besar Regency in the 2017/2018 school year as many as 34 people. The research conducted was a class action research (Classroom Action Research) which was conducted for (3) months, from March to May, in 2 cycles, which became. Each cycle consists of 4 stages, namely planning, action, observation, and reflection. The research data were obtained through learning outcomes tests, observations, interviews and documentation studies. The data analysis technique used in the study was qualitative descriptive analysis. The validity of the data uses the technique of triangulation of data sources. The conclusion of the study is the application of Jigsaw cooperative learning can improve the activities and learning outcomes of students in learning Social Sciences in 11th grade IPS-2 Senior High School Seulimum Aceh Besar Regency in the academic year 2017/2018. The results of observations showed the average indicator of student learning activities in learning Social Sciences in the first cycle was 63.29% and in the second cycle was 87.85%. From cycle I to cycle II it increased by 24.56%. The results of knowledge test material excretion system in humans also increased in the first cycle was 65.67 and in the second cycle 80.51, from cycle I to cycle II increased by 14.84. I was 78.41 and in the second cycle 81.78, from cycle I to cycle II increased by 3, 37. Likewise the teacher's performance in the learning process increased from cycle I by 61.0% and in the second cycle 83.50% increased by 22.50.